2022
DOI: 10.5802/crchim.198
|View full text |Cite
|
Sign up to set email alerts
|

The photocatalytic degradation of a binary textile dyes mixture within a new configuration of loop reactor using ZnO thin film-phytotoxicity control

Abstract: This article is licensed under the Creative Commons Attribution 4.0 International License. http://creativecommons.org/licenses/by/4.0/ Les Comptes Rendus. Chimie sont membres du Centre Mersenne pour l'édition scientifique ouverte www.centre-mersenne.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…While the sample’s crystal structure and growth direction were analyzed using a D8 Bruker Advance X-ray diffractometer with Cu ka radiation (λ = 1.54 nm) and X-ray diffraction (XRD)—Bruker (Billerica, MA, USA). The average crystallite size was obtained from the X-ray line extended analysis using the Debye–Scherrer method [ 33 , 34 ]. The detailed material properties of the ZnO NRs/rGO-based nanorods have been reported in our previous report [ 18 ].…”
Section: Synthesis and Fabrications Methodsmentioning
confidence: 99%
“…While the sample’s crystal structure and growth direction were analyzed using a D8 Bruker Advance X-ray diffractometer with Cu ka radiation (λ = 1.54 nm) and X-ray diffraction (XRD)—Bruker (Billerica, MA, USA). The average crystallite size was obtained from the X-ray line extended analysis using the Debye–Scherrer method [ 33 , 34 ]. The detailed material properties of the ZnO NRs/rGO-based nanorods have been reported in our previous report [ 18 ].…”
Section: Synthesis and Fabrications Methodsmentioning
confidence: 99%
“…Xiao et al showed a 98% RhB removal in solution on activated carbon from white sugar [15]. AOPs as ozonation [16], photocatalysis [17][18][19][20], sono-photocatalysis [3], and ultrasound-assisted TiO 2 photocatalysis [21] presented hopeful results. These methods, although effective, involve the use or production of compounds whose environmental impact is not well known.…”
Section: Introductionmentioning
confidence: 99%